Cancer Aging Research Group (CARG) score in older adults undergoing curative intent chemotherapy: a prospective cohort study. Issue 6 (29th June 2021) - Ostwal, Vikas; Ramaswamy, Anant; Bhargava, Prabhat; Hatkhambkar, Tejaswee; Swami, Rohit; Rastogi, Sameer; Mandavkar, Sarika; Ghosh, Jaya; Bajpai, Jyoti; Gulia, Seema; Srinivas, Sujay; Rath, Sushmita; et al.
Abstract : Importance: The Cancer Aging Research Group (CARG) toxicity score is used to assess toxicity risk in geriatric patients receiving chemotherapy. Objective: The primary aim was to validate the CARG score in geriatric patients treated with curative intent chemotherapy in predicting grade 3–5 toxicities. Design: This was a longitudinal prospective observational study. Setting: Tata Memorial Hospital, Mumbai, India, a tertiary cancer care referral centre. Participants: Patients, aged ≥65 years, with gastrointestinal, breast or gynaecological stage I–III cancers being planned for curative intent chemotherapy. A total of 270 patients were required for accrual in the study. Exposure(s): Total risk score ranged from 0 (lowest toxicity risk) to 19 (highest toxicity risk). Main outcome(s) and measure(s): The primary endpoint of the study was to evaluate whether the CARG risk score predicted for grade 3–5 toxicities. Results: The study cohort of 270 patients had a mean age of 69 (65–83) years, with the most common cancers being gastrointestinal (79%). Fifty-two per cent of patients had atleast one grade 3–5 toxicity. The risk of toxicity was increased with an increasing risk score (42% low risk, 51% medium risk and 79% high risk; p<0.001). There was no association between either Eastern Cooperative Oncology Group (ECOG) performance status (p=0.69) or age-adjusted Charlson Comorbidity Index (p=0.79) risk categories and grade 3–5 chemotherapy toxicities. Conclusions and relevance: This study validates the CARG risk score in predicting for grade 3–5 toxicities in geriatric oncology patients receiving curative intent chemotherapy and can be considered as the standard of care before planning chemotherapy in every elderly patient. Trial registration number: CTRI/2016/10/007357; Results.